Structural, Morphological and Photoluminescence Spectroscopy Studies of Intense Blue Ce\(^3+\)-doped Lutetium Oxyorthosilicate Scintillator Nanomaterials - Hamroun, M. S. E.; Guerbous, L.; Bachari, K.; Taibeche, M.; Chebout, R.; Mechernene, L.; Nedjar, A. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
Monoclinic Lu\(_2\)SiO\(_5\)(LSO):Ce\(^3+\) type oxyorthosilicates nanopowders were prepared by sol-gel route. The goal of present work is the study the influence of annealing temperature treatment, up to 1100\(^°\)C, on the structural, morphology and photoluminescence properties of LSO:Ce\(^3+\) nanophosphor. The powder samples were characterized by X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), Room temperature Raman spectroscopy and room temperature photoluminescence spectroscopy. It was found that the annealing temperature treatment has an effect on the phase purity, the morphology as well as photoluminescence characteristics LSO:Ce\(^3+\) nanophosphor. An intense violet-blue asymmetric emission band ranged from 370 nm to 470 nm with a maximum intensity situated at around 420 nm, assigned to the 5d\(→\)4f (\(^2\)F\(_5/2\),\(^2\)F\(_7/2\)) interconfigurational transitions of Ce\(^3+\) ion in LSO nanomaterial has been observed. Furthermore, LSO:Ce\(^3+\) present higher emission intensity for sample annealed at 1200 \(^°\)C. The influences of the presence of LPS, as parasitic phase, on structural, morphological and luminescence properties LSO:Ce\(^3+\) nanomaterial were highlighted. Also, using the experimental data and wave function-based ab-initio calculation results, the Ce\(^3+\) energy levels position relative to the LSO nanomaterial band structure were found.